A case report on a rare occurrence: mesenteric cyst complicating pregnancy - Regupathi, Shri Janani; Janakiraman, Prabha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Mesenteric cysts are very rare abdominal tumours with an incidence of 1/250000 cases and a mere less than 10 cases noted in pregnancy. The etiology is attributed to the failure of communication of lymph nodes to the lymphatics. These cysts can be uni/multilocular and involve the small bowel mesentery. An 18 year old primigravida at 12 weeks of gestation was admitted with complaints of lower abdominal pain for 1 month. Ultrasound revealed the presence of loculated ascites or a mesenteric cyst. MRI abdomen revealed a large well defined cystic lesion with thick septations suggestive of a complex ovarian cyst/ mesenteric cyst. Patient was planned for laparotomy. On laparotomy, the patient had 2 large mesenteric cysts with intervening bowel. Fluid aspirate from the cyst was turbid/chylolymphatic. Laparotomy was proceeded to excision of the cyst with resection and anastomosis of the bowel. Post operatively, there were no complications noted at the site of anastomosis, an ultrasound showed a live fetus with good cardiac activity and adequate growth. She carried the fetus to term with no maternal and fetal complications and was terminated by caesarean section. A very large cyst may affect the growth of the fetus, may rupture spontaneously or may undergo torsion. The definitive treatment is enucleation with/without bowel resection. Early identification and definitive treatment is necessary for proper management of the condition.